2014
DOI: 10.1007/s11099-014-0068-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementary potassium nitrate on growth and gas-exchange characteristics of salt-stressed citrus seedlings

Abstract: We investigated the effects of supplementary KNO 3 and NaCl on one-year-old, potted Valencia orange (Citrus sinensis) scions grafted on Iranian mandarin Bakraii [Citrus reticulata × Citrus limetta] (Valencia/Bakraii) and Carrizo citrange [C. sinensis × Poncirus trifoliata] (Valencia/Carrizo) rootstocks. After watering plants for 60 days with 50 mM NaCl, the lowest reduction in dry mass, stomatal conductance, and chlorophyll (Chl) content was found in Valencia/Bakraii. Bakraii accumulated more Cland Na + in roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…The dissipation of excitation energy, determined as NPQ, is one of the ways that most photosynthetic mechanisms resist the adversity (Misra, Latowski, & Strzalka, ). Increased NPQ in response to NaCl treatment was observed in several plants, such as Citrus reticulata seedlings (Khoshbakht, Ghorbani, Baninasab, Naseri, & Mirzaei, ) and Morus alba (Yu et al, ). The OJIP analysis of Spirulina platensis showed that the fluorescence yield of J, I and P phases decreased sharply with the increase of salt concentration, and qP decreased when qN increased (C. Lu & Vonshak, ).…”
Section: Photosynthetic Pigmentmentioning
confidence: 99%
“…The dissipation of excitation energy, determined as NPQ, is one of the ways that most photosynthetic mechanisms resist the adversity (Misra, Latowski, & Strzalka, ). Increased NPQ in response to NaCl treatment was observed in several plants, such as Citrus reticulata seedlings (Khoshbakht, Ghorbani, Baninasab, Naseri, & Mirzaei, ) and Morus alba (Yu et al, ). The OJIP analysis of Spirulina platensis showed that the fluorescence yield of J, I and P phases decreased sharply with the increase of salt concentration, and qP decreased when qN increased (C. Lu & Vonshak, ).…”
Section: Photosynthetic Pigmentmentioning
confidence: 99%
“…Salinity stress has received increasing attention in recent years because it greatly reduces agricultural productivity (Parihar et al 2015). Salinity causes various injuries in plants, such as tissue burning, yield reduction, and finally plant death (Romero-Aranda et al 2001), causes leaf senescence, reduction PSII activities (Khayyat et al 2016), enhances membrane permeability (Dhindsa et al 1981), nutritional imbalances, and toxicity (Khoshbakht et al 2014). NaCl inhibits photosynthetic rate (PN) as a consequence of osmotic stress, which leads to a decrease in water potential and stomatal conductance (g s ), sugar accumulation, which causes feedback inhibition, and ion toxicity (e.g., an excess of Na + and Cl -) accompanied by a reduction of K + and Ca 2+ (Khoshbakht and Asgharei 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Al-Hamzawi (2010) has reported that the application of 15 mM KNO 3 considerably improved growth parameters by increasing plant height, leaves number, and total leaf area of cucumber. Supplementary KNO 3 under NaCl salt-stressed treatments had increased leaf number, leaf area, stem elongation, and dry matter in grafted citrus (Khoshbakht et al, 2014). Despite the positive effects mentioned in most growth parameters (Table 2), salinity induced by KNO 3 + BNS that is prolonged until the fruiting stage has resulted in a lower leaf number.…”
Section: Effect Of Salinity Sources On Growthmentioning
confidence: 91%